(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2008)
A small collection of echinoids from the Eastern Desert of Jordan includes the species Clypeaster biarritzensis, Amphiope? sp., Echinolampas cherichirensis, and Eupatagus meslei. This fauna closely resembles faunas of early Oligocene age from North Africa. The presence of the associated foraminifera Nummulites intermedius and N. fichteli dates the upper portion of the Wadi Shallala Formation exposed in the area of Wadi Al Ghadaf as early Oligocene (Rupelian), younger than the generally accepted middle (Bartonian) to late Eocene (Priabonian) age of this formation. The presence of rocks of this age in Jordan along what was probably the southern margin of the Tethyan Seaway is evidence that communication between the eastern and western provinces of the Western Tethys Region still existed in this area at this time.